Determinants of substance use among young people attending primary health centers in India - U. Venkatesh; P. Aparnavi; K.A. Mogan; R. Durga; Jennifer Pearson; Surekha Kishore; Hari Shanker Joshi; Naveen Sukumaran Nair; B. Nisha; Renu Agrawal; Karavadi Vidusha; C. Vankhuma Chenkual; et al. (Cambridge Prisms: Global Mental Health, 2024)
Abstract